Technical Efficiency of the Generation of Knowledge in the European Union (2003-2010) - Agüeros Manuel; Casares-Hontañón Pedro; Coto-Millán Pablo; Ángel Pesquera Miguel (Bulletin of Geography. Socio-Economic Series)
This paper analyses the determinants of knowledge in the European Union of the 27, through estimates of transcendental logarithmic production functions (translog) in different scenarios. For this, a data panel for the period 2003-2010 has been elaborated, selecting the production stochastic frontier as the most reliable model to estimate technical efficiency for European innovation. The empirical result is that technological capital, human capital and relational capital have a positive and significant influence on the generation of knowledge. Also, from the observation of results we can assure that the size (in terms of population) of a country within the EU-27 does not positively influence the technical efficiency of knowledge production.